2017
DOI: 10.1038/s41598-017-17737-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of promoting effect of a novel Cu-bearing metal stent on endothelialization process from in vitro and in vivo studies

Abstract: Drug eluting stents (DES) have been extensively applied nowadays and reduce the incidence of in-stent restenosis (ISR) greatly as compared with bare metal stents (BMS). However, the development of DES is hindered by the risk of late stent thrombosis (LST) due to delayed re-endothelialization, while endothelialization is an important process related to ISR and LST after implantation. 316L is a traditional stent material without bioactivity and have a high risk of ISR. Cu is recognized for angiogenesis stimulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Therefore, the surface of N/Cu–Ti releases more copper ions than that of Cu–Ti. Copper ions in the concentration range of 10 mg/L are not cytotoxic and can promote HUVECs proliferation while killing bacteria effectively. Copper ions release from the surface of Cu–Ti and N/Cu–Ti is less than 10 mg/L, so more Cu 2+ with save limit could enter into the microenvironment between the surface of sample and cells or bacteria, improving the angiogenic performance and antibacterial ability of the sample surface. , The “synergistic effect” of N/Cu dual implantation could have a good antibacterial effect and endow Ti with good angiogenic performance at the same time.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the surface of N/Cu–Ti releases more copper ions than that of Cu–Ti. Copper ions in the concentration range of 10 mg/L are not cytotoxic and can promote HUVECs proliferation while killing bacteria effectively. Copper ions release from the surface of Cu–Ti and N/Cu–Ti is less than 10 mg/L, so more Cu 2+ with save limit could enter into the microenvironment between the surface of sample and cells or bacteria, improving the angiogenic performance and antibacterial ability of the sample surface. , The “synergistic effect” of N/Cu dual implantation could have a good antibacterial effect and endow Ti with good angiogenic performance at the same time.…”
Section: Results and Discussionmentioning
confidence: 99%
“…52−55 Copper ions release from the surface of Cu−Ti and N/Cu−Ti is less than 10 mg/L, so more Cu 2+ with save limit could enter into the microenvironment between the surface of sample and cells or bacteria, improving the angiogenic performance and antibacterial ability of the sample surface. 46,47 The "synergistic effect" of N/Cu dual implantation could have a good antibacterial effect and endow Ti with good angiogenic performance at the same time.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…After absorption, Cu is transported into the liver and throughout the body through the blood. Apart for some Cu-containing proteins are stored in the liver, and the rest are synthesized in liver or other human tissues, such as cytochrome oxygenase and monoamine enzyme [ 8 , 15 ]. More than 90 different enzymes and proteins have been found to contain Cu to various extents [ 16 , 17 ].…”
Section: Cu An Essential Trace Elementmentioning
confidence: 99%
“…They further found that vascular smooth muscle cells and vascular endothelial cells tended to undergo apoptosis to some degree when the Cu concentration was over 7.5 μg/ml. Moreover, Jin et al implanted 316L-Cu bare metal stents (BMS), drug-eluting stents (DES), and 316L BMS into swine to evaluate the re-endothelialization ability in vivo ; their results demonstrated that 316L-Cu BMS showed the best effect on endothelialization along with good biosafety [ 15 ]. Previous studies have shown that copper containing metal materials with copper content of 3-5 wt% could promote the endothelialization and inhibit the growth of smooth muscle cells [ 5 , 48 , 49 , 51 , 52 ].…”
Section: Beneficial Effects Of Cu On the Cardiovascular Systemmentioning
confidence: 99%
“…In addition, N/Cu-Ti [ 53 ] and C/Cu-Ti [ 51 ] have excellent biocompatibility with MC3T3-1 ( Figure 3 c,g). Moreover, Cu ion can improve the angiogenic properties [ 54 ] of the Ti surface and promote the proliferation and migration of HUVESCs. Other strategies, including Cu/Zn [ 46 , 55 ] ion co-implantation, can also improve the mechanical properties and antimicrobial capacity of the sample surfaces.…”
Section: Preparation Techniques and Related Properties Of Cu-doped Ti...mentioning
confidence: 99%